The Role of Energy Flux in Weight Management - Clemens Drenowatz; Klaus Greier (Exercise Medicine, 2017)
Excess body weight has been identified as one of the leading threats to public health. In addition to health concerns at the individual level, the increased medical costs put a significant burden on the health care system. Even though an imbalance between energy intake and energy expenditure is ultimately responsible for changes in body weight and body composition such a simple opposition does not reflect the complex interaction of various contributors to energy balance. The limited understanding of the regulation of energy balance is also reflected by rising obesity levels, despite considerable efforts. In addition to energy balance, energy flux, which represents the rate of energy intake and energy expenditure, has been suggested to play an important role in the regulation of energy balance. Particularly a higher energy flux has been associated with a better matching of energy intake and energy expenditure resulting in stable body weight. While a high energy flux has been traditionally attributed to increased levels of physical activity it should be considered that increased body weight also affects energy expenditure and accordingly energy flux. In fact, total daily energy expenditure, and accordingly energy flux, does not differ between people in industrialized countries, living a predominantly sedentary lifestyle and people following a traditional lifestyle, characterized by high physical activity even though there are significant differences in body weight and body composition. It can, therefore, be argued that energy flux, rather than energy balance is a physiologically regulated entity. In this situation body weight and physical activity levels work in opposition to maintain a constant energy flux and weight gain would be a means to maintain a high energy flux with a sedentary lifestyle.